EFEKTIVITAS PELAKSANAAN PEMBATASAN KEGIATAN MASYARAKAT MIKRO DALAM MENGURANGI MOBILITAS MASYARAKAT KELURAHAN UWURAN DUA KECAMATAN AMURANG KABUPATEN MINAHASA SELATAN - ACHMAD, ARES MENANDAR; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2023)
The purpose of this study was to determine the effectiveness of the implementation of restrictions on micro community activities in reducing community mobility in Uwuran Dua Village, Amurang District, South Minahasa Regency. begins by reviewing all available data from various sources, both interviews and recording of documents. Data analysis in this study begins with carrying out the process of data reduction, data interpretation and drawing conclusions. The results of the study show that the implementation of Micro-scale Community Activity Restrictions (PPKM) is solely for the benefit of the community, nation and state. In addition to the effort to accelerate the termination of the Covid-19 distribution chain, it is also an effort to restore the nation’s economy and fulfill community needs. So it can be concluded that the Government is able to adapt the Implementation of Micro-scale Community Activity Restrictions (PPKM) in serving the community at the Uwuran Dua sub-district office. Keywords: Effectiveness, Implementation of Community Activity Restrictions